Cannabis use among middle and high school students in Ontario: a school-based cross-sectional study - Sampasa-Kanyinga, Hugues; Hamilton, Hayley A.; LeBlanc, Allana G.; Chaput, Jean-Philippe (Université d'Ottawa | University of Ottawa, 2018)
Cannabis use can have serious detrimental effects in children and adolescents. It is therefore important to continually assess the use of cannabis among young people in order to inform prevention efforts. We assessed the prevalence of cannabis use among middle and high school students in Ontario and examined its association with demographic and behavioural factors.